The impact of quality of institutions on health expenditures, health outcomes and economic growth in the Sub-Saharan African countries - Aliyu, Sa'ad Shamduddeen (2017)
This study investigates the impact of quality of institutions on health expenditures, health outcomes and economic growth in the sub-Saharan African countries. While other parts of the world are living longer and healthier, mortality rate in Sub-Saharan Africa has remained the highest. This research is motivated by the increasing disparities in Sub-Saharan African’s health, their spending on health and their contribution to economic growth with the rest of the world. The data used in this study is secondary data from four different sources. Health outcomes indicators including life expectancy, infant and under-five mortality were sourced form World Health Organization (WHO), Development Assistance for health to non-governmental organizations was sourced from Institute for Health Matrix and Evaluation (IHME), institutions variables (Voice and accountability, regulatory quality, control of corruption, political stability and absence of violence, rule of law and regulatory quality) were sourced from World Governance indicators (WGI). All other indicators representing public and private health expenditures, demographic structures, health service delivery, income per capita, disease patter, capital formation, literacy rate, fiscal space and environmental quality were from World Bank World development indicators (WDI). Generalized method of moment was used to evaluate the impact of quality of institutions on health expenditures, health outcomes and economic growth in the sub-Saharan African countries. Diagnostic tests and robustness checks were conducted for all the estimated models to ensure reliability and efficiency of the estimates. The result of the impact of institutions on health expenditures reveals that both aggregated and disaggregated institutions have positive impact on health spending but that control of corruption, voice and accountability as well as rule of law have a greater impact on health spending. On the impact of institutions on health outcomes, institutions were found to have a negative effect on under-five and infant mortality and positive effect on life expectancy. The effect of institutions when interacted with public health spending increases the effect of health expenditures on health outcomes. This means that funds allocated for health would be better utilized to purchase basic health care package or provide basic health care services to the people with improvement in the quality of institutions. Lastly, on economic growth, the study shows that though the region is among the fastest growing economies, income per capita is still the lowest and resources are concentrated in the hands of few individuals who have strong links to the governments. The general findings suggests that an increase in the quality of institutions improve health spending, health outcomes and economic growth. This study, makes policy recommendations to stake holders on the need to strengthen institutions by promoting the rule of law, controlling corruption, improving management quality and accountability of resources for health, cutting down bureaucracy in the provision of health care services and ensuring political stability and violence free society. This will increase efficiency and effectiveness in the purchase of health care services, increase life expectancy through an improved utilization of health care services and increase the people’s contribution to wealth creation in the region.